MO337: Higher Antibody Response After 2 Vaccinations With MRNA-1273 as Compared With BNT162B2 and AZD1222 in High-Risk Kidney Patients. (3rd May 2022) - Bouwmans, Pim; Messchendorp, Lianne; Imhof, Celine; Sanders, Jan-Stephan; Hilbrands, Luuk; Vart, Priya; Reinders, Marlies; Bemelman, Frederike; Abrahams, Alferso C; Dorpel van den, René; Ten Dam, Marc; De Vries, Aiko; et al.
Abstract: BACKGROUND AND AIMS: Lower antibody responses after SARS-Cov-2 vaccination have been reported in patients with severely impaired kidney function or patients with kidney replacement treatment. We compared humoral responses and reported adverse events of three vaccines (mRNA-1273, BNT162b2 and AZD1222) in kidney transplant recipients (KTRs), dialysis patients, patients with CKD stages G4–G5 and control subjects without kidney disease. METHOD: KTRs, dialysis patients and patients with CKD stages G4–G5 were vaccinated with either mRNA-1273, BNT162b2 or AZD1222 during the Dutch SARS-CoV-2 vaccination program. Control subjects were all vaccinated with mRNA-1273. Blood samples were obtained at 1 month after two vaccinations by home-based finger prick tests and were analysed for the presence of IgG antibodies against the receptor-binding domain of the spike protein of SARS-CoV-2 using the Sanquin anti-SARS-CoV-2 RBD IgG ELISA assay. Primary endpoints were the antibody titer and reported systemic adverse events (AEs) at 1 month after the second vaccination. Multivariate regression analysis was performed on the difference between vaccines with respect to antibody titer and AEs after correction for sex, ethnicity, BMI, eGFR, dialysis vintage, transplantation characteristics and use of immunosuppressive drugs. RESULTS: A total of 2468 KTRs, 480 dialysis patients, 400 patients with CKD stages G4–G5 and 186 control subjects were enrolled. KTRs had lower antibody titers (66 [8–573] BAU/mL) in comparison to dialysis patients [1375 (431–2896) BAU/mL], patients with CKD stages G4–G5 [2097 (828–4077) BAU/mL] and control subjects [3713 (2291–6451) BAU/mL]. mRNA-1273 demonstrated a higher antibody titer compared with BNT162b2 in KTR [72 (9–638) versus 21 (6–128) BAU/mL; P  < .001), dialysis patients [1675 (573–3031) versus 636 (216–1416) BAU/mL; P  < .001] and patients with CKD stages G4–G5 [2879 (1425–5311) versus 1063 (389–1939) BAU/mL; P  < .001). In a similar pattern, mRNA-1273 demonstrated a higher antibody titer compared with AZD1222 ( P  < .001 in all groups). Multivariate analysis revealed that BNT162b2 and AZD1222 were significantly associated with lower antibody levels compared with mRNA-1273 in all 3 patient groups. BNT162b2 demonstrated less frequently systemic AEs compared with mRNA-1273 in KTRs (12% versus 27%; P  < .001), dialysis patients (12% versus 29%; P  = .007) and in patients with CKD G4–G5 (18% versus 67%, P  < .001). AZD1222 demonstrated less systemic AEs compared with mRNA-1273 only in patients with CKD stages G4–G5 (39% versus 67%; P  = .03). Multivariate analysis revealed that BNT162b2 was associated with fewer systemic AEs in only dialysis patients ( P  = .04) and patients with CKD stages G4–G5 ( P  = .02). CONCLUSION: mRNA-1273 demonstrated significantly higher antibody levels at 1 month after 2 vaccinations as compared with BNT162b2 and AZD1222 in high-risk patients with kidney disease. BNT162b2 was associated with a fewer systemic AEs in dialysis patients and patients with CKD stages G4–G5, although these AEs were mild and self-limiting. mRNA-1273 may therefore be considered as the preferred SARS-CoV-2 vaccine in high-risk patients with kidney disease. Whether the higher antibody response following vaccination with mRNA-1273 sustains and results in a better protection against COVID-19 is yet to be analysed.